Realidade, sujeito e sentido como unidade concreta: do antipsicologismo à ontologia fenomenológica de "O ser e o nada" - Paes, Gabriel Gurae Guedes (Universidade Federal de São Carlos, 2021)
In the first chapter of the first part of The Being and the Nothing, “The origin of the negation”, Sartre distinguishes the abstract negation, merely judicative, from the real negation that occurs when I do not meet Pedro at the bar. This distinction is not secondary, but fundamental to understand that being-in-the-world is not divisible between representation on the one side and the reality of the world on the other. The world is a totality (not totalized, but it is a process of totalization) that constitutes human reality itself. In this totality there is no subject on one side and reality on the other, because it is in reality that we constitute our own being. Reality, as a human reality, occurs as a situation in the world. Between the abstraction of judicial denial and real denial in a situation such as not meeting Pedro at the bar, we were led to explore the difference not only between negative judgment and real denial, but also between the sense of the situation and the sense of judgment in general. Our aim is to show that sense, as a sense of a real situation in the world - as opposed to the referential sense of judgment - is a sense of a real subject that is inseparable from reality as a world. And to understand what reality is and what we mean, we go back to the sartrian works of phenomenological psychology ”prior to Being and Nothingness. In these works, Sartre declares himself an "antipsychologist", that is, he takes a stand against psychological conceptions that intend to transform consciousness (as imagination, perception, thought, emotion, etc.) into fact. Consciousness is not a fact, but a condition for the facts to present themselves as facts regulated within scientific hypotheses. There is an ontological variation of this antipsychology in Being and Nothingness that is expressed in the argument that we are not a thing with meaning, but giving meaning, not as a judicial act, but as a real action in a real situation. The sense, for having no basis for the action itself, is an unfounded foundation. If meaning is made in action, it would be absurd to want to make sense of the action, because we cannot make sense of the meaning as if it were a thing or a fact. An ontological experience of this observation occurs in anguish. And to say that we are real subjects in a real world, we have to show that reality is not identical with objectivity. Reality occurs not only as a thing or as a fact, but also as a condition for understanding the world as the world in which there are things and facts. In this way, the subject is a real subject, but not as a thing or fact. Thus, before analyzing a conception of the real meaning of a real subject, communicate a triple movement: (1) Show that consciousness is not a fact and at the same time (2) show that reality is not limited to the fact, in the end, (3) thinking about a real subject that is not factual. And so that the subject, as a constituent of meaning, is not divided between representation on the one hand and reality on the other, it is necessary to show that sense, as an existential sense, occurs immediately as an action in the world. To enter Sartrian “psychology phenomenology” he chooses The Imaginary, because in this work we can elucidate what Sartre understands by reality in relation to Husserl's idealism. And to understand the existential meaning in its relationship with the world, it will be inevitable to resort to Heidegger's Being and time.
Réalité, sujet et sens comme unité concrète: de l'antipsychologie à l'ontologie phénoménologique de «l'être et le néant»
Keywords: Sentido; Realidade; Imaginário; Sujeito; Fenomenologia; Ontologia; Psicologismo; Sense; Reality; Imaginary; Subject; Phenomenology; Ontology; Psychologism; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA